A New Species of Land-locked Freshwater Shrimp Genus Caridina (Decapoda: Atyidae) from Middle Mekong Basin, Thailand - Macharoenboon, Kongkit; Sutcharit, Chirasak; Siriwut, Warut; Jeratthitikul, Ekgachai (Tropical Natural History, 2023)
A newly discovered freshwater shrimp in the genus Caridina H. Milne-Edwards, 1837 from Thailand is described here as C. panhai sp. nov. The distinctiveness of the new species was supported by both morphological investigation and molecular analysis based on a concatenated dataset of two mitochondrial genes (16S rRNA and COI). Diagnostic characters of the new species include the strongly convex rostrum, very slender carpus of second pereopod (8.11–10.04 times as long as wide), and the reduced epipod on second and third pereopods. Intriguingly, females of C. panhai sp. nov. possess a small number of very large eggs (22–36 eggs per individual), which is characteristic of land-locked species. The new species is the first land-locked Caridina species discovered in Thailand, and its range is restricted to the Middle Mekong Basin in the northeast part of the country. By including historical records, there are 15 species of Caridina found in Thailand.